Bone mineral density reductions after tenofovir disoproxil fumarate initiation and changes in phosphaturia: a secondary analysis of ACTG A5224s. (20th March 2017) - Gupta, Samir K.; Yeh, Eunice; Kitch, Douglas W.; Brown, Todd T.; Venuto, Charles S.; Morse, Gene D.; Ha, Belinda; Melbourne, Kathleen; McComsey, Grace A.
Abstract: Background: It is unknown if the greater reductions in bone mineral density (BMD) associated with initiation of tenofovir disoproxil fumarate compared with abacavir in previously untreated HIV-infected participants in the ACTG A5224s clinical trial were associated with potentially worsening tenofovir-related phosphaturia. Methods: We correlated changes in BMD at the hip and spine with changes in phosphaturia [transtubular reabsorption of phosphorus (TRP) and tubular maximum phosphate reabsorption per glomerular filtration rate (TmP/GFR)] from entry through week 96 in those initiating tenofovir ( n  =   134) versus abacavir ( n  =   135) with efavirenz or atazanavir/ritonavir in A5224s. We also correlated changes in BMD with tenofovir AUC measured between weeks 4 and 24. Results: Changes in TRP and TmP/GFR through week 96 between the tenofovir and abacavir arms were not significantly different (both P  ≥   0.70) and did not differ with use of efavirenz versus atazanavir/ritonavir. There were no significant correlations between changes in either TRP or TmP/GFR and with either hip or spine BMD in the tenofovir arms. Tenofovir AUC was significantly correlated with changes in hip BMD, but not spine BMD, at week 24 ( r  =   −0.22, P  =   0.028) and week 48 ( r  =   −0.26, P  =   0.010), but not at week 96 ( r  =   −0.14, P  =   0.18). Conclusions: Changes in phosphaturia were not different between the tenofovir and abacavir arms in A5224s. Changes in hip and spine BMD with tenofovir were not related to changes in phosphaturia. However, tenofovir exposure was weakly associated with changes in hip BMD through week 48.